The effect of Korean wave on body image and eating disorders among female adolescents in Yogyakarta, Indonesia - Nurina Umy Habibah; A Fahmy Arif Tsani; Sumarni DW (Jurnal Gizi Klinik Indonesia, 2021)
Background: Currently, Indonesia is one of the countries affected by the Korean "fever" due to the Korean wave's globalization through the media. The content of K-pop which displays model characteristics that are identical to a slender body, tall, and attractive, can lead to adolescent body image perception. The problem most often experienced by adolescents is physical appearance. The negative body image in adolescence could encourage the emergence of eating behavior disorders known as eating disorders. Objective: To analyze the relation between Korean wave exposure through media information with body image and eating disorders risk in female high school students in Yogyakarta. Methods: This research used the cross-sectional method with a quantitative approach. The research population was female first-grade high school students in Yogyakarta. The subjects of 109 female students who are qualified with the inclusion criteria: enrolled students in the selected schools, physically healthy, and willing to take part in the research; are requested to fill out the Korean wave exposure questionnaire to measure the type and frequency of exposure, the Contour Drawing Rating Scale questionnaire to measure the body image, and the Eating Attitude Test 26 to determine the eating disorders risk. Data were analyzed with the Chi-Square test and logistic regression test. Results: Univariate analysis showed that 11% of the subject was exposed to Korean wave with various type of exposure, 88.1% of the issue was dissatisfied with their body and developed negative body image, and 47.7% of the issue was at risk of eating disorders; 53% of them tend to developed diet behavior, 21.04% bulimia, and 25.96% was in oral intake restriction. The multivariate analysis showed that Korean wave exposure (RP=1.6; 95%CI=0.7-10.04) correlates significantly with negative body image perception. Eating disorders risk significantly affected by Korean wave exposure (RP=2.1; 95%CI=0.97-4.63) and body image (RP=2.93; 95%CI=1.25-5.49). Chi-Square analysis showed body image significantly correlates with eating disorders risk (RP=6.2; 95%CI=1.25-5.94). Conclusions: Exposure to Korean waves affected negative body image in female adolescents. On the other hand, Korean wave exposure and body image also affected eating disorder behavior among female adolescents.* Presented at the International Nutrition and Health Symposium (INHESION) on Sunday, November 15th, 2020, in Yogyakarta, organized by HIMAGIKA and the Department of Health Nutrition, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada